Falls among elderly and its relation with their health problems and surrounding environmental factors in Riyadh - Sulaiman A Alshammari; Abdullatif M Alhassan; Matar A Aldawsari; Faisal O Bazuhair; Fahad K Alotaibi; Ahmed A Aldakhil; Faroq W Abdulfattah (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Falls among the elderly are one of the major causes of morbidity and mortality worldwide. They constitute the second leading cause of unintentional deaths after road-traffic accidents. The aim of the study was to estimate the prevalence of falls among the elderly and to investigate the factors that contribute to this phenomenon. MATERIALS AND METHODS: A cross-sectional analytical study was conducted in the elderly, over the age of 60, in Riyadh. The sample under scrutiny was estimated to be 357 in total. A pilot study was conducted among 15 subjects. Two questionnaires were used for the interviews which were translated into Arabic using the "Morse Fall Scale." The questionnaires assessed: the participants' previous history of falls, whether a secondary diagnosis had been obtained, whether any ambulatory aids had been used or whether an IV connection had been fitted during convalescence. They also inquired if any gait/transferring device had been used to assist the patient at any time. RESULTS: Out of 357 participants, 206 (57.7%) had a history of falls. Study found an association between the number of falls recorded, the age of the participants, and whether the participant was female. Furthermore, there were statistically significant associations between the history of falls and a condition of impaired health. The results also showed that environmental hazards play a significant role in the occurrence of falls with P ≤ 0.001, in which 103 (81.7%) of the individuals who were exposed to environmental hazards revealed a history of falls. CONCLUSION: Falls among the elderly are common. Significantly, if the health of the individuals is impaired, and there are contiguous environmental risk factors, these elements combine to play a part in the occurrence of such falls. There is, therefore, a need to design and develop a health awareness program to prevent such problems in the elderly.